A Linear Fragment of Unacylated Ghrelin (UAG6−13) Protects Against Myocardial Ischemia/Reperfusion Injury in Mice in a Growth Hormone Secretagogue Receptor-Independent Manner - Huynh, David N.; Elimam, Hanan; Bessi, Valérie L.; Ménard, Liliane; Burelle, Yan; Granata, Riccarda; Carpentier, André C.; Ong, Huy; Marleau, Sylvie (Frontiers in Endocrinology, 2019)
Unacylated ghrelin (UAG), the most abundant form of ghrelin in circulation, has been shown to exert cardioprotective effect in experimental cardiopathies. The present study aimed to investigate the cardioprotective effect of a linear bioactive fragment of UAG against myocardial ischemia-induced injury and dysfunction in C57BL/6 wild type mice and the mechanisms involved. Treatments were administered at doses of 100 (UAG), 1000 and 3000 (UAG6-13) nmol/kg at 12 h interval during 14 days prior to 30 min left coronary artery ligation and reperfusion for a period of 6 or 48 h. The infarct area was decreased in a dose-dependent manner at 48 h of reperfusion, with a reduction of 54% at the highest dose of UAG6-13 tested. Myocardial hemodynamics were improved as demonstrated by an increase in cardiac output, maximum first derivative of left ventricular pressure, and preload recruitable stroke work, a load-independent contractility index. Six hours after reperfusion, circulating levels of IL-6 and TNF-α pro-inflammatory cytokines were reduced, and the effect was maintained at 48 h for TNF-α. 5' AMP-activated protein kinase (AMPK) was activated, while acetyl-CoA carboxylase (ACC) activity was inhibited, along with a decrease in apoptotic protein levels. In isolated hearts, the effect of UAG6-13 was unaffected by the presence of D-Lys3–GHRP-6, a ghrelin receptor (GHSR1a) antagonist, suggesting that the peptide acted through a GHSR1a-independent pathway. The results support the therapeutic application of UAG bioactive peptide fragments against myocardial ischemia/reperfusion injury.